2012
DOI: 10.1097/dcr.0b013e318260d3a0
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Endoscopic Total Mesorectal Excision Combined With Single-Port Laparoscopy

Abstract: Rectal resection via the transanal approach combined with single-port laparoscopic assistance may be easier and safer than the traditional approach, especially in male patients who have a narrow pelvis. More data are needed in order to draw conclusions concerning oncologic results and before selecting the most appropriate indications for this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 25 publications
3
100
0
6
Order By: Relevance
“…Neoadjuvant treatment was given to 81% of patients for locally advanced tumors (Table 1). 104,[107][108][109][110][111][112][113][114][115] Mean operative time was 272.5 min (range 120-460), with a mean of 2.8 abdominal trocars used (range 1-5), mean estimated blood loss of 77.8 mL (range 10-300), and mean LOS of 10.2 days (range . The overall intraoperative complication rate was 8.3%, including a 2.8% incidence of conversion to open surgery.…”
Section: Notes Transanal Rectosigmoid Resection: Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neoadjuvant treatment was given to 81% of patients for locally advanced tumors (Table 1). 104,[107][108][109][110][111][112][113][114][115] Mean operative time was 272.5 min (range 120-460), with a mean of 2.8 abdominal trocars used (range 1-5), mean estimated blood loss of 77.8 mL (range 10-300), and mean LOS of 10.2 days (range . The overall intraoperative complication rate was 8.3%, including a 2.8% incidence of conversion to open surgery.…”
Section: Notes Transanal Rectosigmoid Resection: Clinical Trialsmentioning
confidence: 99%
“…Her ileostomy has since been reversed with good functional outcomes and no evidence of recurrence to date. Since this initial case, several small clinical series of TME for rectal cancer using a transanal NOTES approach with laparoscopic assistance have been published, [107][108][109][110][111][112][113] highlighting variations in patient selection, surgical technique, complications, and outcomes.…”
Section: Notes Transanal Rectosigmoid Resection: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The macroscopic quality of TME was documented in all published reports, except in study of Wolthuis et al [103] and has been reported as ''intact'' [110] , ''adequate'' [111,112] , ''satisfactory'' [104,113] , or ''complete'' [11,12,106,107,111,114] .…”
Section: Oncological Outcomesmentioning
confidence: 99%
“…Atallah et al published the first series of TAMIS-TME in 20 patients with rectal cancer [2]. Although evidence on the efficacy of TAMIS-TME in rectal cancer has been accumulating [3,4]. there is scarce data on its use in inflammatory bowel disease.…”
Section: Introductionmentioning
confidence: 99%